# Sin(4x)cos(7x)=-(cos(4x)sin(7x))

## Simple and best practice solution for Sin(4x)cos(7x)=-(cos(4x)sin(7x)) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for Sin(4x)cos(7x)=-(cos(4x)sin(7x)) equation:

Simplifying
Sin(4x) * cos(7x) = -1(cos(4x) * sin(7x))
Remove parenthesis around (4x)
inS * 4x * cos(7x) = -1(cos(4x) * sin(7x))
Remove parenthesis around (7x)
inS * 4x * cos * 7x = -1(cos(4x) * sin(7x))
Reorder the terms for easier multiplication:
4 * 7inS * x * cos * x = -1(cos(4x) * sin(7x))
Multiply 4 * 7
28inS * x * cos * x = -1(cos(4x) * sin(7x))
Multiply inS * x
28inxS * cos * x = -1(cos(4x) * sin(7x))
Multiply inxS * cos
28cinosxS * x = -1(cos(4x) * sin(7x))
Multiply cinosxS * x
28cinosx2S = -1(cos(4x) * sin(7x))
Remove parenthesis around (4x)
28cinosx2S = -1(cos * 4x * sin(7x))
Remove parenthesis around (7x)
28cinosx2S = -1(cos * 4x * ins * 7x)
Reorder the terms for easier multiplication:
28cinosx2S = -1(4 * 7cos * x * ins * x)
Multiply 4 * 7
28cinosx2S = -1(28cos * x * ins * x)
Multiply cos * x
28cinosx2S = -1(28cosx * ins * x)
Multiply cosx * ins
28cinosx2S = -1(28cinos2x * x)
Multiply cinos2x * x
28cinosx2S = -1(28cinos2x2)
Remove parenthesis around (28cinos2x2)
28cinosx2S = -1 * 28cinos2x2
Multiply -1 * 28
28cinosx2S = -28cinos2x2
Solving
28cinosx2S = -28cinos2x2
Solving for variable 'c'.
Move all terms containing c to the left, all other terms to the right.
Add '28cinos2x2' to each side of the equation.
28cinosx2S + 28cinos2x2 = -28cinos2x2 + 28cinos2x2
Combine like terms: -28cinos2x2 + 28cinos2x2 = 0
28cinosx2S + 28cinos2x2 = 0
Factor out the Greatest Common Factor (GCF), '28cinosx2'.
28cinosx2(S + s) = 0
Ignore the factor 28.
Subproblem 1Set the factor 'cinosx2' equal to zero and attempt to solve:
Simplifying
cinosx2 = 0
Solving
cinosx2 = 0
Move all terms containing c to the left, all other terms to the right.
Simplifying
cinosx2 = 0
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
Subproblem 2Set the factor '(S + s)' equal to zero and attempt to solve:
Simplifying
S + s = 0
Solving
S + s = 0
Move all terms containing c to the left, all other terms to the right.
Add '-1S' to each side of the equation.
S + -1S + s = 0 + -1S
Combine like terms: S + -1S = 0
0 + s = 0 + -1S
s = 0 + -1S
Remove the zero:
s = -1S
Add '-1s' to each side of the equation.
s + -1s = -1S + -1s
Combine like terms: s + -1s = 0
0 = -1S + -1s
Simplifying
0 = -1S + -1s
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
The solution to this equation could not be determined.`